Variable flux permanent magnet for automobile application - Ong, Ian Tiong Yen (Nanyang Technological University, 2022)
This paper is a Final-Year Project report on variable flux Permanent Magnets (PM) for automobile application. Research done has shown that many different variations of PM motors are used and highly applicable in Electric Vehicle (EV) applications. This paper focus on the research and study of a Six Phase hybrid Excited Flux Switching E-core machine, with an emphasis on Back-Electromotive Force (EMF) and torque performance. The JMAG program was used during this project to recreate and simulate studies on all models, conditions were made as similar as possible to ensure the most objective results.